Does the Effect of Replacing Cottonseed Meal with Dried Distiller’s Grains on Nellore Bulls Finishing Phase Vary between Pasture and Feedlot? - Alvair Hoffmann; Andressa Scholz Berça; Abmael da Silva Cardoso; Natalia Vilas Boas Fonseca; Maria Luísa Curvelo Silva; Rhaony Gonçalves Leite; Ana Cláudia Ruggieri; Ricardo Andrade Reis (Animals, 2021)
The study aimed to evaluate the effect of replacing cottonseed meal by dried distiller’s grains (DDG) in terms of efficiency in the productive aspects of beef cattle finishing in pasture versus feedlot. The experiment was conducted in a completely randomized design in a 2 × 3 factorial arrangement, with two production systems (pasture versus feedlot) and three supplements: CM, conventional supplement with cottonseed meal (CM) as a protein source; 50DDG: supplement with 50% replacement of CM by DDG; and 100DDG: 100% replacement. The effect of replacing CM by DDG on dry matter and nutrients intake and nutrients digestibility depends on the finishing system (p < 0.05). While in the pasture system animal consumed more nutrients in the CM, a greater intake was observed in the 100DDG in feedlot. The nutrients digestibility was lower in the pasture (p < 0.05). Animal performance and final body weight were higher in the feedlot (p < 0.0001), with averages of 1.57 kg/d and 566 kg of final body weight (FBW) for feedlot, and 0.99 kg/d and 504 kg FBW for pasture. The use of DDG does not change the animal performance finished in pasture or feedlot, and it is a viable alternative to replace conventional supplements in finishing phase in both systems in tropical environment.